Genetics of type III hyperlipoproteinemia - Feussner, Giso; Piesch, Susanne; Dobmeyer, Jürgen; Fischer, Christine (Genetic epidemiology, 1997)
One hundred forty-seven relatives of 43 patients with “classical” type III hyperlipoproteinemia (HLP) having the apolipoprotein (apo) E2/2 phenotype were studied to determine the occurrence of hyperlipidemia and the presence of further possible genes for lipoprotein disorders in these families. In 12 pedigrees primary dyslipidemia was prevalent among patients and respective blood-relatives. In these kindreds the coexistent presence of genes for familial combined hyperlipidemia (n = 6), familial hypertriglyceridemia (n = 5), and familial hypercholesterolemia (n = 1), respectively, was supposed. Our results, therefore, confirm and extend previous data on the multifactorial genesis of the diseases. Besides homozygosity for a receptor binding-defective isoform of apo E (apo E2), additional genes for familial lipoprotein disorders might operate in the pathogenesis of type III HLP. This is the largest family study performed so far in this primary lipoprotein disorder. Genet. Epidemiol. 14:283-297,1997. © 1997 Wiley-Liss, Inc.